Alternative Complement Pathway Inhibition Does Not Abrogate Meningococcal Killing by Serum of Vaccinated Individuals - Ispasanie, Emma; Muri, Lukas; Schubart, Anna; Thorburn, Christine; Zamurovic, Natasa; Holbro, Thomas; Kammüller, Michael; Pluschke, Gerd (Frontiers in Immunology, 2021)
Dysregulation of complement activation causes a number of diseases, including paroxysmal nocturnal hemoglobinuria (PNH) and atypical hemolytic uremic syndrome (aHUS). These conditions can be treated with monoclonal antibodies (mAbs) that bind to the complement component C5 and prevent formation of the membrane attack complex (MAC). While the MAC is involved in uncontrolled lysis of erythrocytes in PNH and aHUS patients, it is also required for serum bactericidal activity (SBA), i.e. clearance of encapsulated bacteria. Therefore, terminal complement blockage in these patients increases the risk of invasive disease by Neisseria meningitidis more than 1000-fold compared to the general population, despite obligatory vaccination. It is assumed that alternative instead of terminal complement pathway inhibition would reduce the risk of meningococcal disease in vaccinated individuals. To address this, we investigated the SBA with alternative complement pathway inhibitors. Serum was collected from adults before and after vaccination with a meningococcal serogroup A, C, W, Y capsule conjugate vaccine and tested for meningococcal killing in the presence of factor B, factor D, C3, C5 and MASP-2 inhibitors. As expected, inhibition of C5 abrogated killing of meningococci by all sera. In contrast, both factor B and D inhibitors affected meningococcal killing in sera from individuals with low, but not with high bactericidal anti-capsular IgG titers. While the anti-MASP-2 mAb did not impair SBA, inhibition of C3 impeded meningococcal killing in most, but not in all sera. These data provide evidence that vaccination can provide protection against invasive meningococcal disease in patients treated with alternative pathway inhibitors.